Congenital Heart Defects: Risk Stratification for Pregnancy - Joserizal Serudji (Andalas Obstetrics And Gynecology Journal, 2022)
Major advances in medicinal and operative therapy on congenital heart defects (CHD) patients have led the majority of affected women survive to childbearing age. The risk of cardiovascular complications during pregnancy and peripartum depends on the type of the underlying defect, the extent and severity of residual haemodynamic lesions and comorbidities. Thuugh pregnancy is well tolerated in patients with CHD, but for some women with particularly high-risk lesions and poor functional class, pregnancy poses significant risk for cardiovascular complications, including premature death. As a result, preconception risk stratification and counseling are mandatory and should be done in all women of childbearing age with CHD. This will enable informed decision making for pregnancy savers.